N-(2,2-Diphenylethyl)furan-2-carboxamide - Iliyan Ivanov; Diyana Dimitrova; Stanimir Manolov (Molbank)
We report the synthesis of N-(2,2-diphenylethyl)furan-2-carboxamide. The compound was fully characterized by melting point determination, 1H and 13C NMR spectroscopy, infrared spectroscopy, and mass spectrometry. The combined analytical data confirm both the successful synthesis and the structural integrity of the target molecule.